Estudo dos parâmetros de processo de dobramento de chapas de aço laminado a quente - Leite, Matheus Foloni (2022)
Among the various processes of sheet metal formability, the folding stands out for its simplicity and replicability, being considered a of the most recurrent operations in metal sheets. In addition, mathematical models were developed providing the understanding of the variables of this process. Thus, the present study sought to explain and calculate equations found in the literature related to some bending parameters, clarifying their influences on the magnitude of the bending force, the recovery elasticity and the force generated at the support points, which can have negative effects such as localized deformation, markings and cracks. The chosen parameters were divided into groups, as follows: related to material properties (limit of yield, tensile strength and elastic modulus), the dimensions of the sheet (thickness, length and width) and to the matrix (U-shaped, L-shaped, V-shaped and their channel opening widths). To help the interpretation of negative effects and numerical results, the mechanical properties (included in the studied property range) of eight types of hot-rolled steel sheets (low carbon, microalloyed and stainless steel) commonly processed by bending were used. It was verified that the magnitude of the maximum bending force reached comes from the higher mechanical properties of the materials, due to the increase in the dimensions of the plate, by the use of a V-shaped matrix with the smallest possible channel opening width. It was shown a greater magnitude of the force generated in the support points of the plate, when added they can reach twice the bending force. The springback was demonstrated by the internal radius of the bend after this phenomenon, presenting small variations that were studied. In view of the above, all the results were discussed and solutions to the problems encountered in this process were proposed.